Principles of supply chain managementand their adaptation to the Asian horticultural sector - Batt, Peter (Agricultural and Food Marketing Association for Asia and the Pacific-AFMA, Curtin Univesrsity of Technology, Department of Agriculture, FAO, 2007)
Supply chain management refers to the coordination and alignment of materials, financial and information flows for all activities and processes involved in a supply chain. Broadly speaking, a supply chain describes the full range of activities that are required to bring a product or service from conception through the different stages of production and processing to deliver superior value to the customer at least cost to the supply chain as a whole. Supply chain management encompasses all those activities associated with sourcing and procurement, production scheduling, order processing, inventory management, warehousing and servicing customers across the many independent firms involved in the distribution of food. While the concept of supply chain management is not new, its application to the fresh produce industry is more recent. Increased competition arising from the deregulation of global markets is forcing food manufacturers and retailers to give greater consideration towards ways of reducing costs while simultaneously fulfilling consumers? demand for superior quality. With the increasing need to assure consumers that the food they intend to consume is safe and nutritious, the food industry is moving away from the traditional means of buying towards a more direct and reliable means of procurement where buyers exert greater control over prices, quality and production methods. Unable to respond to the demands of the institutional buyers, there is a very real risk in the transitional economies that most smallholder farmers will become increasingly marginalized. The lack of incentives, the added costs, the lack of knowledge and the inability to make appropriate investments will inevitably result in a dualistic food distribution system where smallholder farmers will face diminishing returns. To break away from the commodity trap and to enter higher value markets, smallholder farmers need to consolidate and differentiate to add value to their product offer. A range of support mechanisms will be required to overcome many of the impediments and to facilitate this transition.